Rereading of the Quran in Light of Nursi’s Risale-i Nur Collection: Shuhudi Exegesis - Yucel, Salih (Religions, 2021)
The concept of tafsiri şuhudi (transempirical exegesis) was coined for the first time by Said Nursi (d. 1960) and was reflected throughout his works. In his tafsiri şuhudi (pronounced shuhudi) methodology, Nursi views the Qur’an as an interpretation of the universe, that is Kitab al-Kabir (a big book). According to Nursi, such an exegesis is needed to reach the degree of iman tahkiki (investigative belief), also known as authentic faith. As part of his methodology, Nursi uses spiritual experience (kashf) and secular sciences as evidence for gaining true faith. Tafsiri şuhudi is an offshoot of ishari (inner meaning) tafsir but one that is injected with rationalism. This tafsir type also injects witnessing (şuhudi) into the dry body of scientific and modern tafsir that emerged in the Muslim world after European enlightenment. This article first examines the original hermeneutical concept of tafsir şuhudi in Nursi’s works and then analyses the sound heart, an essential part of iman tahkiki, in light of Nursi’s transempirical experience. The article argues that Nursi injects rationalism into the ishari tafsir methodology and infuses şuhudi experience by making it not only an epistemic but also an existential understanding of modern tafsir methodology.